Beyond congruence measures for the evaluation of personality factor structure replicability: An exploratory structural equation modeling approach. (October 2015) - Perera, Harsha N.; McIlveen, Peter; Burton, Lorelle J.; Corser, Diane M.
Highlights: We illustrate an overarching approach to the evaluation of factor replicability based on ESEM methods. The ESEM approach overcomes the known limitations of congruence measures. The ESEM approach is demonstrated in the context of examining NEO-FFI factor invariance across gender. Evidence is also obtained for the criterion validity of the NEO-FFI scores. Abstract: The present study aims to illustrate an encompassing approach to the evaluation of personality factor structure replicability based on novel exploratory structural equation modeling (ESEM) methods. This approach comprises formal tests of measurement invariance applied to the flexible ESEM framework and overcomes the limitations of congruence measures that have traditionally been used to assess factor replicability in personality research. On the basis of 1566 responses to the widely-used NEO Five-Factor-Inventory (NEO-FFI), we demonstrate this ESEM approach in the context of examining the invariance of the NEO-FFI factor structure across gender. The approach is shown to converge with traditional congruence measures and extend these measures for examining factorial structure consistency. In addition, more general replicative data supporting the validity of the NEO-FFI are reported. We discuss the ESEM approach as a viable alternative to the congruence approach and acknowledge some important limitations of the method.